Post-1994 South African Education: The Challenge of Social Justice. Issue 1 (March 2014) - Badat, Saleem; Sayed, Yusuf
The formal end of apartheid was greeted with optimism and expectations. A new Government of National Unity with Nelson Mandela at its head signaled a new just and democratic social order, including social justice in and through education. Twenty years later, formally desegregated yet class-based educational institutions, continuing disparities and inequities, and poor academic achievement are key features of the contemporary educational order. This article considers how far South Africa has come since 1994 in realizing laudable constitutional and policy goals, especially equity, quality, and social justice in education. It argues, however, that, as a consequence of policy, the doors of learning remain firmly shut to the majority of South Africans. Some key strategies to advance social justice are identified. A failure to act now and with urgency to reform South Africa's educational approach betrays constitutional ideals and leaves intact the systemic crisis of education that especially affects South Africa's historically disadvantaged and marginalized peoples.